Potential of floating solar technology in Malaysia - Jamalludin, Mohd Alif Saifuddin; Sukki, Firdaus Muhammad; Bakar, Siti Hawa Abu; Ramlee, Fadzliana; Munir, Abu Bakar; Bani, Nurul Aini; Muhtazaruddin, Mohd Nabil; Mas’ud, Abdullahi Abubakar; Rey, Jorge Alfredo Ardila; Ayub, Ahmad Syahrir; Sellami, Nazmi (Institute of Advanced Engineering and Science, 2019)
Solar energy is a natural source of energy and is tremendously abundant. The concept of floating solar is to fulfil and to support the existing energy supply in order to enhance the human life. The floating solar exploits the massive availability of ocean region and the severe unavailability of land. The main purpose of this paper is to evaluate the potential of floating solar to be deployed in coastal or infield in Malaysia. It was predicted that such system could generate around 14,530 MWh per annum in Malaysia. It can be concluded that floating solar could be one of the most important ocean structures in the future because it is reliable, flexible and has virtually low cost production comparing with other ocean structures. © 2019 Institute of Advanced Engineering and Science. All rights reserved.